Preliminary Potential and Characteristics Study of Microalgae from Intensive Shrimp Pond in North Aceh District as Renewable Energy - Prama Hartami; Eva Ayuzar; Munawar Khalil; Muhammad Hatta; Aulia Utari; Rahayu (LPPM Universitas Malikussaleh, 2022)
Microalgae are organisms that have many variations of species that are very suitable to be developed in all Indonesian waters for use as food, medicine, and biofuels. The method used in this research is a survey method, which is a descriptive study to describe/describe the nature of a phenomenon/condition that existed at the actual time and examine the causes of certain symptoms. The stages of this research include determining the location of the research, data collection techniques, and data analysis of the results of the studies that have been carried out. The data analysis in question was in the form of statistical analysis to compare the proximate content in the form of lipids, starch, and sucrose from microalgae from each sampling location. Correlation tests were also carried out between water nutrient variables, the dominance of microalgae species, and the proximate content of microalgae when sampling was carried out. The results showed that the microalgae species that grew and dominated the media included Skeletonema, Chaetoceros, Diatomae, and Chlorella.